2000
DOI: 10.1016/s0002-9440(10)65089-4
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 and Angiopoietin-2 Activate Trophoblast Tie-2 to Promote Growth and Migration during Placental Development

Abstract: Human placental development involves coordinated angiogenesis and trophoblast outgrowth that are compromised in intrauterine growth restriction (IUGR). As Tie-2(؊/؊) mice exhibit growth retardation and vascular network malformation, the expression of Tie-2 and its ligands, angiopoietin-1 (Ang-1) and angiopoietin-2 (Ang-2), were investigated in human placenta from normal pregnancies and those complicated by severe IUGR. Ribonucleotide protection assays showed no significant change in the expression of Ang-2 mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
121
1
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(138 citation statements)
references
References 30 publications
(58 reference statements)
10
121
1
6
Order By: Relevance
“…Doppler velocimetry measures of the umbilical artery support the concept of increased placental vascular resistance [46], similar to what has been reported for early-onset severe FGR in humans [25,26,28]. Furthermore, similar as to what has been reported for term human FGR pregnancies [36,37], fetal cotyledon VEGF, VEGF-R1 Ang 2, and Tie 2 expression is reduced in our near-term sheep FGR pregnancies [45,47]. By contrast, at day 55 p.c.…”
Section: Placental Development In Compromised Pregnanciessupporting
confidence: 88%
See 1 more Smart Citation
“…Doppler velocimetry measures of the umbilical artery support the concept of increased placental vascular resistance [46], similar to what has been reported for early-onset severe FGR in humans [25,26,28]. Furthermore, similar as to what has been reported for term human FGR pregnancies [36,37], fetal cotyledon VEGF, VEGF-R1 Ang 2, and Tie 2 expression is reduced in our near-term sheep FGR pregnancies [45,47]. By contrast, at day 55 p.c.…”
Section: Placental Development In Compromised Pregnanciessupporting
confidence: 88%
“…Greater expression of Ang 2 during the first trimester, with Ang 1 and VEGF expression increasing from early to late gestation [35], fits with the concept that branching angiogenesis occurs during early placental development, followed by nonbranching angiogenesis [29]. The altered placental morphology (i.e., long straight terminal villi) associated early-onset severe FGR may result from increased non-branching angiogenesis, as both VEGF and Ang 2 are reduced in term placenta from this type of pregnancy [36,37], consistent with reduced branching angiogenesis during late gestation.…”
Section: Placental Development In Compromised Pregnanciessupporting
confidence: 65%
“…As in baboons of the present study, Ang-1 assessed by in situ hybridization was expressed in high level within the cytotrophoblast and syncytiotrophoblast of the human placenta, where expression also was decreased in late gestation [20]. Also, as shown in baboons, Ang-2 assessed by laser densitometric analysis and immunocytochemistry was localized within villous trophoblast and perivascular tissue of the human placenta [20][21][22][23], where levels showed only a small increase with advancing gestation [20]. In contrast, Ang-2 mRNA levels determined by PCR and Northern blot analysis in whole villous tissue decreased with advancing human [22] and marmoset [24] gestation.…”
Section: Discussionsupporting
confidence: 76%
“…In vitro experiments have shown that Ang1 has speci®c e ects on endothelial cells: it potently induces chemotactic response (Witzenbichler et al, 1998), network formation , sprouting (Koblizek et al, 1998;Kim et al, 1999) and survival in apoptosis Kim et al, 2000a). Although a recent report indicates that Ang2 (250 ng/ml) stimulates proliferation, migration, and release of nitric oxide in trophoblast cells that are expressing the Tie2 receptor (Dunk et al, 2000), the role of Ang2 on cultured endothelial cells is not known.…”
mentioning
confidence: 99%